Relationship Between Substance Abuse And Knowledge, Attitude, And Behavior Among Adolescents At Kuala Langat, Selangor - Muhamad Firdaus Bin Abu Talib
This dissertation identifies the level and comparison the level of knowledge, attitudes and behaviors among adolescents towards substance abuse issue by comparison and relationship among the variables (Gender, Age, Level of Education, Social Economic Status (SES) and Substance Misuse such as cigarette and inhalant). This study involved 204 respondents randomly selected among adolescents living at Kuala Langat Districts, Selangor. The instruments of Substance Abuse Knowledge, Attitude and Behavior Survey Questionnaire were used and converted in the google form for data collection tools. Data has been analyzed using the Statistical Package for Social Science (SPSS) version 27.0. The findings showed that there was significant difference in knowledge with gender, education level and substance misuse, significant difference in attitude with SES and significant difference in behavior with age and SES. Subsequently, the results of the study also show a moderate level of adolescents in knowledge, low level in attitude and low level of behavior towards substance abuse. Educational initiatives on substances abuse is pivotal to increase the level of knowledge and awareness of the effects of substance abuse and also aiming at changing the attitudes which influence adolescents behaviors as well as building their social and personal skills.